A rare case of serologically diagnosed overlap syndrome presents as an idiopathic inflammatory myositis without any overlapping features - Patel, Disha; Patel, Darsh; Parikh, Prachi; Patel, Parth (International Journal of Research in Medical Sciences, 2023)
Overlap syndrome is a rare inflammatory rheumatic condition that shares features suggestive of at least two distinct autoimmune diseases with a reported prevalence of less than 34/100,000 persons and an incidence of less than 20/million/year. One example of an overlap syndrome is the presence of dermatomyositis or polymyositis with other autoimmune afflictions such as systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), or Sjogren’s syndrome. We present a case report of a 22-year-old male presented with progressive weakness in both upper and lower limbs without any other significant complaints. On investigation, serology revealed antibodies suggestive of overlap syndrome, which on further investigations, categorized as idiopathic inflammatory myositis (IIM). This shows that overlap syndrome, as an IIM, is one of the differential diagnoses in patients presenting with progressive extremity weakness involving both extremities even if there is no involvement of any sensory function.